A burr-shaped polyacrylamide nanosphere and its preparation method and application

By preparing burr-like polyacrylamide nanospheres and using thiolated PAMAM-loaded metal copper quantum dots, the problem of existing polyacrylamide microspheres being difficult to move deeply and improve oil displacement rates in oil fields is solved, and effective sealing, dissection adjustment and oil displacement effect are improved in the deep strata.

CN119176912BActive Publication Date: 2025-04-08SUZHOU CHUXIN MOYI TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411699768.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-04-08
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

Although existing polyacrylamide microspheres have significant driving effect in oil field applications, the question of whether they can be moved deeper into the formation and how to improve the oil flooding rate still needs further research.

Method used

By adjusting the morphology and size of the polymer microspheres, burr-like polyacrylamide nanospheres were prepared, and thiolated PAMAM was used as the matrix-loaded metal copper quantum dots to initiate polymerization to prepare nanospheres. This method improves the sealing strength and regulation ability of nanospheres, and enhances its stability in high temperature and high salt environments.

Benefits of technology

It realizes effective sealing and regulation of deep strata, improves oil displacement and recovery, and nanospheres have good shear resistance, salt resistance and temperature resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176912B_ABST
    Figure CN119176912B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of nanomaterials, and in particular, relates to a burr-shaped polyacrylamide nanosphere and a preparation method and application thereof. The present invention uses thiolated PAMAM as a matrix to load copper quantum dots to initiate polymerization of acrylamide monomers to prepare nanoscale polymer microspheres. Since PAMAM has a high degree of geometric symmetry, by introducing dense thiol functional groups on the surface of PAMAM, a strong coordination bond can be formed with metal copper quantum dots, and the quantum dots can be evenly fixed on the outer surface of PAMAM. The characteristics of spherical particles lead to uneven polymerization rate on the surface of thiolated PAMAM loaded with metal copper quantum dots, which promotes the formation of burr-shaped nanosphere morphology. After the burr-shaped nanospheres absorb water and swell, they can not only play a role in cross-linking and interlocking to improve the plugging efficiency, but also the burr-shaped tip structure can play a role similar to a brush, reducing the force between oil droplets and rocks and the flow resistance of crude oil in the reservoir, thereby improving the recovery rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano materials, and in particular relates to a burr-shaped polyacrylamide nanosphere and a preparation method and application thereof. Background Art

[0002] Chemical profile control technology for water injection wells can control the depth profile of the reservoir, directly plug the high permeability layer, move the injected fluid to the low permeability layer, improve the heterogeneity of the reservoir, and increase the coverage of the liquid entering the formation, so as to achieve the purpose of improving the ultimate recovery of crude oil. At present, the more commonly used profile control agents at home and abroad include weak gel, colloidal dispersion gel, pre-crosslinked expanded particles, microorganisms and foam profile control agents, and polymer microspheres. Among them, the polymer microspheres are mainly polyacrylamide microspheres. As a new type of profile control agent for deep reservoir development, it has been widely used in major oil fields because of its excellent hydrophilicity, swelling and viscoelasticity. The particle size of the polymer microspheres with excellent performance can reach the nanometer level and the size is adjustable. The microspheres can be directly added to the injected water and the produced water of the oil field. Under the injection pressure, they can absorb formation water. After swelling with water, they can migrate in the porous medium of the reservoir and pass through the oil layer that ordinary profile control agents cannot reach. It plays a role in deep profile control and has strong applicability, simple operation, convenience and environmental protection.

[0003] As a high molecular organic compound, polyacrylamide microspheres can achieve the characteristics of stability and unchanged particle size when encountering oil, and will absorb water and expand when encountering water, thereby increasing the particle size. In practical applications, polyacrylamide microspheres are continuously moved deep into the formation by the driving force of water injected into the formation. During this period, the water absorption and expansion effect of the microspheres will gradually increase their volume and block the high permeability channels and large channels, so that subsequent water cannot pass through the channels, which plays a role in changing the flow direction of the formation liquid.

[0004] Field tests have shown that polyacrylamide microspheres have a significant oil-displacement effect in oilfield applications, but further research is needed on whether polyacrylamide microspheres can migrate to deeper formations and how to improve oil recovery rates.

[0005] Quantum dots are a new type of semiconductor nanomaterial, a type of semiconductor nanoparticle composed of II-VI or III-V elements with a radius smaller than or close to the exciton Bohr radius. Due to the influence of quantum size effect and dielectric confinement effect, quantum dots have unique properties, which makes quantum dots have great application potential in the fields of oil extraction and catalysis. The prior art generally directly uses quantum dots as tracers or oil displacement agents, and the application range is relatively narrow. CN115306362A directly uses quantum dots as oil displacement agents, and uses the extremely strong penetration and oil washing effects of quantum dots to penetrate into the rock surface to remove the oil film and improve the oil washing efficiency; however, its cost is relatively high, and it does not have the effect of blocking and regulating displacement. CN115181217A prepares core-shell microspheres with fluorescent tracing function, by introducing fluorescent quantum dots in the process of preparing the core microsphere solution, and then mixing and adsorbing with the shell monomer water to prepare the core-shell microsphere solution. The fluorescent quantum dots are located inside the core-shell fluorescent microspheres and will not detach, thereby improving the subsequent detection accuracy. The quantum dot microspheres are prepared into microspheres of ordinary morphology by direct in-situ polymerization process, and only the tracer function of quantum dots is used for detection, and the plugging and flooding effect is limited. The fluorescent microspheres prepared by CN117736722A, CN115247060A, etc. have smooth surfaces and cannot be used as flooding agents. Summary of the invention

[0006] The purpose of the present invention is to provide a burr-shaped polyacrylamide nanosphere and its preparation method and application in view of the defects of the prior art. By adjusting the morphology and size of the polymer microspheres, the polymer microspheres have the characteristics of easy injection, high plugging strength and strong adjustment ability, and have good shear resistance, salt resistance and temperature resistance, good expansion performance, and can achieve the purpose of deep plugging and profile adjustment of the formation.

[0007] To achieve the above object, the present invention provides the following technical solution: a method for preparing burr-shaped polyacrylamide nanospheres, comprising the following steps:

[0008] (1) adding thiolated PAMAM to a metallic copper quantum dot solution, performing ultrasonic dispersion, and drying to obtain thiolated PAMAM loaded with metallic copper quantum dots; the mass ratio of the metallic copper quantum dots to the thiolated PAMAM is (0.001-0.05):1;

[0009] (2) dispersing the thiol-PAMAM loaded with metal copper quantum dots and a surfactant in an organic solvent and stirring evenly to obtain a premixed solution;

[0010] (3) Add acrylamide and acrylic acid monomers and a cross-linking agent to the premixed solution and stir evenly; and heat the premixed solution under the protection of an inert gas to obtain burr-shaped polyacrylamide nanospheres.

[0011] In the previous work (CN118580443A), the inventor used silica of different particle sizes as reinforcing fillers and prepared polyacrylamide microspheres by dispersion polymerization, which improved the heat resistance and salt resistance of the microspheres to a certain extent. However, the microspheres have a large particle size, a relatively smooth surface, weak interaction between microspheres, and limited plugging and flooding effects. Subsequently, the inventors prepared lychee-shaped or rambutan-shaped polyacrylamide microspheres by loading copper oxide or metallic copper quantum dots. Although the above-mentioned polymer microspheres have certain heat resistance and salt resistance, they have a large particle size or short "tentacles", and the improvement in oil displacement capacity is limited. In order to further improve the plugging and flooding capacity of polymer microspheres, the present invention introduces a dendritic PAMAM (polyamide-amine) polymer with a thiol end group as a matrix, and prepares a thiol-loaded PAMAM.

[0012] PAMAM is a typical dendrimer. Compared with other traditional dendrimers, PAMAM has a large number of surface functional groups, intramolecular cavities and nanometer-scale dimensions, which provide a basis for loading copper quantum dots. Since the hydrocarbon chains in the PAMAM dendrimer are lipophilic groups, but the carboxyl and amino groups it contains are hydrophilic groups, it not only has the effect of solubilization and stabilization, but can also combine with copper quantum dots through electrostatic adsorption; on the other hand, the presence of a large number of cavities on the surface and inside of PAMAM also helps to load copper quantum dots.

[0013] However, directly using PAMAM cavities and electrostatic adsorption as the binding force for loading metal copper quantum dots will lead to uneven loading of metal copper quantum dots, unable to form a spatially ordered structure, and the binding force is weak, which will cause the quantum dots to fall off during the stirring process, affecting the stability of the product structure. In order to improve the stability and uniformity of PAMAM-loaded metal copper quantum dots, the present invention selects a dendritic PAMAM (polyamide-amine) polymer with a thiol end group as a matrix to load metal copper quantum dots. Compared with functional groups such as carboxyl and amino groups, thiol groups have a very strong coordination effect with copper metal. PAMAM ligands containing thiol groups can firmly bind to quantum dots and can be used as stabilizers to prepare stable quantum dot dispersions. Since PAMAM has a high degree of geometric symmetry, the active groups on its surface are evenly distributed, and the surface becomes more and more crowded with the growth of generations. By introducing dense thiol functional groups on the surface of PAMAM, strong coordination bonds can be formed with metal copper quantum dots, and the quantum dots can be evenly fixed on the outer surface of PAMAM.

[0014] Compared with copper oxide quantum dots, metal copper quantum dots are more active; and because of their large surface area to volume ratio, the copper atoms exposed on the surface can provide a large number of active sites, thereby enhancing catalytic activity. The unpaired electrons of metal copper quantum dots can be conjugated with the double bonds of acrylamide monomers, and free radicals can be generated to initiate polymerization reactions without the need for chemical initiators. Under heating conditions, the initiation rate is accelerated while the monomer conversion rate is also accelerated. Compared with the previous technology of loading copper oxide quantum dots with large-particle-size mesoporous microspheres and preparing microspheres with azo substances as initiators, the nanospheres prepared by the polymerization of copper quantum dots loaded with thiol-PAMAM as a matrix in the present invention have a smaller particle size, and truly prepare nanoscale polymer microspheres. Moreover, the present invention does not require the addition of an initiator, and because the monomer undergoes a polymerization reaction on the surface of the metal copper quantum dots, one end of the quantum dots is combined with PAMAM, and the catalytic activity is low; while the catalytic activity of the exposed end is higher. At the same time, since the copper quantum dots are evenly distributed on the outer surface of PAMAM, as the polymerization proceeds, the polymer shell becomes thicker and thicker, the catalytic effect of the quantum dots gradually weakens, and the polymerization rate gradually decreases; further, the quantum dots themselves are granular structures, and there are roughly the same gaps between the evenly distributed quantum dots, while the gaps between the particles have a lower catalytic effect. Therefore, the characteristics of spherical particles lead to uneven polymerization rates. Compared with the uneven distribution of copper quantum dots caused by directly using PAMAM as the matrix, it can promote the formation of burr-like nanosphere morphology, and finally prepare burr-like polyacrylamide nanospheres.

[0015] Compared with the "rambutan"-shaped nanospheres prepared directly by PAMAM loaded quantum dots, the burr-like structure can not only play the role of cross-linking and interlocking to improve the plugging efficiency, but also the burr-like tip structure can play a role similar to a brush, thereby improving the recovery rate. The burr-shaped polyacrylamide nanospheres are small in size and can enter the cracks of reservoir rocks. Under the Brownian motion and electrostatic repulsion, the burr-shaped structure is conducive to the nanospheres to form a wedge-shaped area between the rock surface and the oil droplets. The burr-shaped polyacrylamide nanospheres of uniform size follow the principle of overall entropy reduction and spontaneously arrange in order near the solid / oil / water three-phase contact line, forming a structural separation pressure in the restricted area, which prompts the contact line to move forward continuously. With the flow of nanofluids, a large number of particles accumulate at the front end, which can generate a large pressure at the vertex, separating the oil droplets from the rock. At this time, under the action of the reservoir rock surface, the burr-shaped polyacrylamide nanospheres can be further adsorbed and form an interfacial film, which prevents the oil droplets from re-adhering to the rock surface with the help of the barrier effect of the film. The formation of structural separation pressure reduces the interaction force between oil droplets and rocks and the flow resistance of crude oil in the reservoir, thereby improving the recovery rate.

[0016] Furthermore, the copper quantum dot solution is a chloroform solution of copper quantum dots; the ultrasonic power is 100-200W, and the ultrasonic temperature is 35-45°C.

[0017] Furthermore, the specific preparation process of the thiolated PAMAM in step (1) is: adding thioglycolic acid or methyl thioglycolate to the aqueous solution of amino PAMAM, stirring for reaction, and drying under reduced pressure to obtain the thiolated PAMAM.

[0018] Furthermore, the amino PAMAM is a PAMAM of 4-10 integer generations. The PAMAM with ethylenediamine as the core of the present invention is synthesized by diffusion method. First, the central core ethylenediamine and methyl acrylate are subjected to complete Michael addition reaction to obtain a half-generation PAMAM with an ester end group; the second step is the amidation reaction of the ester end group half-generation PAMAM with excess ethylenediamine to obtain a 1st generation PAMAM with an amino end group. Repeating the above two steps can obtain PAMAMs of different integer generations that are constantly growing. The outer layer of the integer generation PAMAM dendrimer has a large number of amino groups, and the hydrocarbon chain inside it is a lipophilic group, so PAMAM has the dual role of a carrier and a surfactant. The amino active groups on the surface of PAMAM are combined with the metal copper quantum dots using thiol compounds as a connecting bridge, which, on the one hand, reduces the surface energy of the metal copper quantum dots and improves their dispersibility; on the other hand, it can prevent the metal copper quantum dots from being oxidized or agglomerated, and improve the stability of the metal copper quantum dots in the solvent.

[0019] Furthermore, the molar ratio of the amino group on the aminated PAMAM to the thioglycolic acid or methyl thioglycolate is 1:(1.1-1.5).

[0020] Furthermore, the stirring reaction temperature is 45-55° C. and the reaction time is 7-10 h.

[0021] Furthermore, in step (2), the surfactant is polyvinyl pyrrolidone; and in step (3), the crosslinking agent is N,N-methylenebisacrylamide. Since the PAMAM dendrimer has a large number of hydrophilic groups such as ester groups and amide groups, it exhibits strong hydrophilicity. In order to improve the dispersion performance of PAMAM in organic solvents, the present invention deliberately disperses the thiolated PAMAM loaded with metal copper quantum dots and the surfactant used in the acrylamide polymerization process in an organic solvent in advance to prepare a premixed solution; polar molecules such as acrylamide and acrylic acid monomers, N,N-methylenebisacrylamide crosslinking agents, etc. can be prevented from combining with the metal copper quantum dots in advance to prevent affecting the stability of the quantum dots in the solution and the dispersion of the thiolated PAMAM loaded with metal copper quantum dots.

[0022] Furthermore, the temperature of the heating reaction in step (3) is 55-75°C and the time is 2-6h. Furthermore, the reaction temperature is 60-70°C. If the reaction temperature is too low, it is not conducive to the initiation of polymerization of the metal copper quantum dots, and the reaction rate is low; if the reaction temperature is too high, the reaction heat cannot be dispersed in time, and implosion is likely to occur, which is not conducive to the formation of burr morphology.

[0023] Furthermore, the amounts of thiolated PAMAM loaded with metal copper quantum dots, surfactant, acrylamide, acrylic acid, and crosslinking agent are respectively: 1 part of thiolated PAMAM loaded with metal copper quantum dots, 1-3 parts of surfactant, 10-15 parts of acrylamide, 5-10 parts of acrylic acid, and 1-3 parts of crosslinking agent by mass. Furthermore, the crosslinking agent is 1.5-2.2 parts, and moderate crosslinking can not only improve the strength of the nanospheres, but also improve the elasticity of the nanospheres, so that it can take into account both the rigid blocking and elastic displacement capabilities.

[0024] Furthermore, the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 1-2h;

[0025] Furthermore, the average particle size of the burr-shaped polyacrylamide nanospheres is 10-80nm; further, the average particle size of the burr-shaped polyacrylamide nanospheres is 10-60nm; in particular, the average particle size of the burr-shaped polyacrylamide nanospheres is 10-50nm or 10-30nm. The particle size of the burr-shaped polyacrylamide nanospheres can be adjusted by adjusting the PAMAM generation number and the polymerization reaction time. On the basis of ensuring the mechanical properties of the burr-shaped polyacrylamide nanospheres, their plugging and oil displacement capabilities are improved.

[0026] On the other hand, the present invention also provides an application of burr-shaped polyacrylamide nanospheres as a profile control and oil displacement agent. Acrylamide-based polymers are synthetic polymers used to enhance oil displacement. They have excellent rheological properties and are one of the most commonly used polymers in oil displacement applications. Due to the presence of a strong hydrophilic group, the amide group, the polyacrylamide nanospheres have good water absorption and swelling properties. They can absorb water and swell in the deep reservoir, plug the gaps, increase the volume of injected fluids, and thus improve the recovery rate. In order to enhance the stability of polymer nanospheres in the harsh environment of high temperature and high salt in the reservoir, the main monomer acrylamide (AM) and the functional monomer acrylic acid (AA) are copolymerized, and an appropriate amount of cross-linking agent is added to prepare acrylamide-based quantum dot copolymer nanospheres with a cross-linked structure. Compared with the previous "rambutan"-shaped nanospheres, the burr-like structure can not only play a role in cross-linking and interlocking to improve the plugging efficiency, but also the burr-shaped tip structure can play a role as a brush to improve the recovery rate.

[0027] Beneficial effects: The nanospheres prepared by the polymerization initiated by loading copper quantum dots with thiol-PAMAM as the matrix of the present invention have a smaller particle size, and nanoscale polymer microspheres are truly prepared. Since PAMAM has a high degree of geometric symmetry, by introducing dense thiol functional groups on the surface of PAMAM, a strong coordination bond can be formed with the metal copper quantum dots, and the quantum dots can be evenly fixed on the outer surface of PAMAM. The unpaired electrons of the metal copper quantum dots can be conjugated with the double bonds of the acrylamide monomer, and a free radical-initiated polymerization reaction can be generated without a chemical initiator. The quantum dots themselves are granular structures, and there are the same gaps between the uniformly distributed quantum dots, while the catalytic effect of the gaps between the particles is lower. Therefore, the characteristics of the spherical particles lead to uneven polymerization rates, which can promote the formation of burr-like nanosphere morphology relative to the unevenly distributed metal copper quantum dots. Compared with the previous "rambutan"-shaped nanospheres, the burr-like structure can not only play a role in cross-linking and interlocking to improve the plugging efficiency, but also the burr-like tip structure can play a role in brushes to improve the recovery rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a scanning electron micrograph of polyacrylamide nanospheres prepared in Example 12;

[0029] Figure 2 This is a scanning electron microscope image of polyacrylamide nanospheres prepared in Comparative Example 1;

[0030] Figure 3 This is a scanning electron microscope image of the polyacrylamide nanospheres prepared in Comparative Example 2. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Example 1

[0033] A method for preparing burr-shaped polyacrylamide nanospheres comprises the following steps:

[0034] (1) Adding thiolated PAMAM to a chloroform solution of metallic copper quantum dots with an average particle size of 3 nm, ultrasonically dispersing, and drying to obtain thiolated PAMAM loaded with metallic copper quantum dots; the mass ratio of the metallic copper quantum dots to the thiolated PAMAM is 0.005:1; the ultrasonic power is 100 W, and the ultrasonic temperature is 45°C; the specific preparation process of the thiolated PAMAM is: adding methyl thioglycolate to the aqueous solution of the aminated PAMAM, stirring the reaction, and drying under reduced pressure to obtain the thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.1; the stirring reaction temperature is 45°C, and the reaction time is 10 hours;

[0035] (2) Dispersing the thiolated PAMAM loaded with metal copper quantum dots and the surfactant polyvinyl pyrrolidone in an organic solvent, stirring evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 1 hour;

[0036] (3) Add acrylamide and acrylic acid monomers and crosslinking agent N,N-methylenebisacrylamide to the premixed solution and stir evenly; and under the protection of inert gas, heat the reaction to obtain burr-shaped polyacrylamide nanospheres; the heating reaction temperature is 60°C and the time is 6 h; the amounts of thiolated PAMAM loaded with metallic copper quantum dots, surfactant, acrylamide, acrylic acid, and crosslinking agent are as follows by mass: 1 part of thiolated PAMAM loaded with metallic copper quantum dots, 1 part of surfactant, 11 parts of acrylamide, 5 parts of acrylic acid, and 1.5 parts of crosslinking agent.

[0037] Example 2

[0038] A method for preparing burr-shaped polyacrylamide nanospheres comprises the following steps:

[0039] (1) Add thiolated PAMAM to a chloroform solution of metal copper quantum dots with an average particle size of 3 nm, disperse by ultrasonication, and obtain thiolated PAMAM loaded with metal copper quantum dots after drying; the mass ratio of the metal copper quantum dots to the thiolated PAMAM is 0.05:1; the ultrasonic power is 200 W, and the ultrasonic temperature is 35°C; the specific preparation process of thiolated PAMAM is as follows: add methyl thioglycolate to the aqueous solution of aminated PAMAM, stir the reaction, and dry under reduced pressure to obtain thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.5; the stirring reaction temperature is 55°C, and the reaction time is 7h;

[0040] (2) Dispersing the thiolated PAMAM loaded with metal copper quantum dots and the surfactant polyvinyl pyrrolidone in an organic solvent, stirring evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 2 hours;

[0041] (3) Add acrylamide and acrylic acid monomers and cross-linking agent N,N-methylenebisacrylamide to the premixed solution and stir evenly; and heat the reaction under the protection of inert gas to obtain burr-shaped polyacrylamide nanospheres; the heating reaction temperature is 70°C and the time is 2 h; the amounts of thiolated PAMAM loaded with metallic copper quantum dots, surfactant, acrylamide, acrylic acid, and cross-linking agent are as follows by mass: 1 part of thiolated PAMAM loaded with metallic copper quantum dots, 3 parts of surfactant, 15 parts of acrylamide, 10 parts of acrylic acid, and 2.2 parts of cross-linking agent.

[0042] Example 3

[0043] A method for preparing burr-shaped polyacrylamide nanospheres comprises the following steps:

[0044] (1) Add thiolated PAMAM to a chloroform solution of metallic copper quantum dots with an average particle size of 3 nm, disperse by ultrasonication, and obtain thiolated PAMAM loaded with metallic copper quantum dots after drying; the mass ratio of the metallic copper quantum dots to the thiolated PAMAM is 0.008:1; the ultrasonic power is 100 W, and the ultrasonic temperature is 35°C; the specific preparation process of thiolated PAMAM is as follows: add methyl thioglycolate to the aqueous solution of aminated PAMAM, stir the reaction, and dry under reduced pressure to obtain thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.4; the stirring reaction temperature is 45°C, and the reaction time is 7h;

[0045] (2) Dispersing the thiolated PAMAM loaded with metal copper quantum dots and the surfactant polyvinyl pyrrolidone in an organic solvent, stirring evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 2 hours;

[0046] (3) Add acrylamide and acrylic acid monomers and crosslinking agent N,N-methylenebisacrylamide to the premixed solution and stir evenly; and heat the reaction under the protection of inert gas to obtain burr-shaped polyacrylamide nanospheres; the heating reaction temperature is 70°C and the time is 3 h; the amounts of thiolated PAMAM loaded with metal copper quantum dots, surfactant, acrylamide, acrylic acid, and crosslinking agent are as follows by mass: 1 part of thiolated PAMAM loaded with metal copper quantum dots, 1.2 parts of surfactant, 10 parts of acrylamide, 10 parts of acrylic acid, and 2.1 parts of crosslinking agent.

[0047] Example 4

[0048] A method for preparing burr-shaped polyacrylamide nanospheres comprises the following steps:

[0049] (1) Add thiolated PAMAM to a chloroform solution of metal copper quantum dots with an average particle size of 3 nm, disperse by ultrasonication, and obtain thiolated PAMAM loaded with metal copper quantum dots after drying; the mass ratio of the metal copper quantum dots to the thiolated PAMAM is 0.01:1; the ultrasonic power is 120 W, and the ultrasonic temperature is 38°C; the specific preparation process of thiolated PAMAM is: add methyl thioglycolate to the aqueous solution of aminated PAMAM, stir to react, and dry under reduced pressure to obtain thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to methyl thioglycolate is 1:1.3; the stirring reaction temperature is 47°C, and the reaction time is 8 hours;

[0050] (2) Dispersing the thiolated PAMAM loaded with metal copper quantum dots and the surfactant polyvinyl pyrrolidone in an organic solvent and stirring evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 1.2 h;

[0051] (3) Add acrylamide and acrylic acid monomers and crosslinking agent N,N-methylenebisacrylamide to the premixed solution and stir evenly; and under the protection of inert gas, heat the reaction to obtain burr-shaped polyacrylamide nanospheres; the heating reaction temperature is 62°C and the time is 3 h; the amounts of thiolated PAMAM loaded with metallic copper quantum dots, surfactant, acrylamide, acrylic acid, and crosslinking agent are as follows by mass: 1 part of thiolated PAMAM loaded with metallic copper quantum dots, 1.5 parts of surfactant, 12 parts of acrylamide, 6 parts of acrylic acid, and 1.7 parts of crosslinking agent.

[0052] Example 5

[0053] A method for preparing burr-shaped polyacrylamide nanospheres comprises the following steps:

[0054] (1) Add thiolated PAMAM to a chloroform solution of metal copper quantum dots with an average particle size of 3 nm, disperse by ultrasonication, and obtain thiolated PAMAM loaded with metal copper quantum dots after drying; the mass ratio of the metal copper quantum dots to the thiolated PAMAM is 0.04:1; the ultrasonic power is 170 W, and the ultrasonic temperature is 43°C; the specific preparation process of thiolated PAMAM is: add methyl thioglycolate to the aqueous solution of aminated PAMAM, stir the reaction, and dry under reduced pressure to obtain thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to methyl thioglycolate is 1:1.2; the stirring reaction temperature is 52°C, and the reaction time is 9h;

[0055] (2) Dispersing the thiolated PAMAM loaded with metal copper quantum dots and the surfactant polyvinyl pyrrolidone in an organic solvent and stirring evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 1.7 h;

[0056] (3) Add acrylamide and acrylic acid monomers and crosslinking agent N,N-methylenebisacrylamide to the premixed solution and stir evenly; and heat the reaction under the protection of inert gas to obtain burr-shaped polyacrylamide nanospheres; the heating reaction temperature is 67°C and the time is 5 h; the amounts of thiolated PAMAM loaded with metal copper quantum dots, surfactant, acrylamide, acrylic acid, and crosslinking agent are as follows by mass: 1 part of thiolated PAMAM loaded with metal copper quantum dots, 2.6 parts of surfactant, 14 parts of acrylamide, 8 parts of acrylic acid, and 2 parts of crosslinking agent.

[0057] Example 6

[0058] A method for preparing burr-shaped polyacrylamide nanospheres comprises the following steps:

[0059] (1) Adding thiolated PAMAM to a chloroform solution of metallic copper quantum dots with an average particle size of 3 nm, ultrasonically dispersing, and drying to obtain thiolated PAMAM loaded with metallic copper quantum dots; the mass ratio of the metallic copper quantum dots to the thiolated PAMAM is 0.02:1; the ultrasonic power is 140 W, and the ultrasonic temperature is 36°C; the specific preparation process of the thiolated PAMAM is: adding methyl thioglycolate to the aqueous solution of the aminated PAMAM, stirring the reaction, and drying under reduced pressure to obtain the thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.3; the stirring reaction temperature is 48°C, and the reaction time is 8.5h;

[0060] (2) Dispersing the thiolated PAMAM loaded with metal copper quantum dots and the surfactant polyvinyl pyrrolidone in an organic solvent and stirring evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 1.3 h;

[0061] (3) Add acrylamide and acrylic acid monomers and crosslinking agent N,N-methylenebisacrylamide to the premixed solution and stir evenly; and under the protection of inert gas, heat the reaction to obtain burr-shaped polyacrylamide nanospheres; the heating reaction temperature is 69°C and the time is 3.2 h; the amounts of thiolated PAMAM loaded with metal copper quantum dots, surfactant, acrylamide, acrylic acid, and crosslinking agent are as follows by mass: 1 part of thiolated PAMAM loaded with metal copper quantum dots, 1.4 parts of surfactant, 12 parts of acrylamide, 7 parts of acrylic acid, and 1.9 parts of crosslinking agent.

[0062] Example 7

[0063] A method for preparing burr-shaped polyacrylamide nanospheres comprises the following steps:

[0064] (1) Adding thiolated PAMAM to a chloroform solution of metallic copper quantum dots with an average particle size of 3 nm, ultrasonically dispersing, and drying to obtain thiolated PAMAM loaded with metallic copper quantum dots; the mass ratio of the metallic copper quantum dots to the thiolated PAMAM is 0.03:1; the ultrasonic power is 160 W, and the ultrasonic temperature is 41°C; the specific preparation process of the thiolated PAMAM is: adding methyl thioglycolate to the aqueous solution of the aminated PAMAM, stirring the reaction, and drying under reduced pressure to obtain the thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.3; the stirring reaction temperature is 53°C, and the reaction time is 7.5h;

[0065] (2) Dispersing the thiolated PAMAM loaded with metal copper quantum dots and the surfactant polyvinyl pyrrolidone in an organic solvent, stirring evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 1.8 h;

[0066] (3) Add acrylamide and acrylic acid monomers and crosslinking agent N,N-methylenebisacrylamide to the premixed solution and stir evenly; and under the protection of inert gas, heat the reaction to obtain burr-shaped polyacrylamide nanospheres; the heating reaction temperature is 66°C and the time is 4.5 h; the amounts of thiolated PAMAM loaded with metallic copper quantum dots, surfactant, acrylamide, acrylic acid, and crosslinking agent are as follows by mass: 1 part of thiolated PAMAM loaded with metallic copper quantum dots, 2.7 parts of surfactant, 12 parts of acrylamide, 9 parts of acrylic acid, and 1.7 parts of crosslinking agent.

[0067] Example 8

[0068] A method for preparing burr-shaped polyacrylamide nanospheres comprises the following steps:

[0069] (1) Adding thiolated PAMAM to a chloroform solution of metal copper quantum dots with an average particle size of 3 nm, ultrasonically dispersing, and drying to obtain thiolated PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to the thiolated PAMAM is 0.02:1; the ultrasonic power is 160 W, and the ultrasonic temperature is 40°C; the specific preparation process of thiolated PAMAM is: adding methyl thioglycolate to the aqueous solution of aminated PAMAM, stirring the reaction, and drying under reduced pressure to obtain the thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.3; the stirring reaction temperature is 50°C, and the reaction time is 8 hours;

[0070] (2) Dispersing the thiolated PAMAM loaded with metal copper quantum dots and the surfactant polyvinyl pyrrolidone in an organic solvent and stirring evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 1.6 h;

[0071] (3) Add acrylamide and acrylic acid monomers and crosslinking agent N,N-methylenebisacrylamide to the premixed solution and stir evenly; and heat the reaction under the protection of inert gas to obtain burr-shaped polyacrylamide nanospheres; the heating reaction temperature is 65°C and the time is 4 hours; the amounts of thiolated PAMAM loaded with metal copper quantum dots, surfactant, acrylamide, acrylic acid, and crosslinking agent are as follows by mass: 1 part of thiolated PAMAM loaded with metal copper quantum dots, 2 parts of surfactant, 13 parts of acrylamide, 7 parts of acrylic acid, and 1 part of crosslinking agent.

[0072] Example 9

[0073] A method for preparing burr-shaped polyacrylamide nanospheres comprises the following steps:

[0074] (1) Adding thiolated PAMAM to a chloroform solution of metal copper quantum dots with an average particle size of 3 nm, ultrasonically dispersing, and drying to obtain thiolated PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to the thiolated PAMAM is 0.02:1; the ultrasonic power is 160 W, and the ultrasonic temperature is 40°C; the specific preparation process of thiolated PAMAM is: adding methyl thioglycolate to the aqueous solution of aminated PAMAM, stirring the reaction, and drying under reduced pressure to obtain the thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.3; the stirring reaction temperature is 50°C, and the reaction time is 8 hours;

[0075] (2) Dispersing the thiolated PAMAM loaded with metal copper quantum dots and the surfactant polyvinyl pyrrolidone in an organic solvent and stirring evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 1.6 h;

[0076] (3) Add acrylamide and acrylic acid monomers and crosslinking agent N,N-methylenebisacrylamide to the premixed solution and stir evenly; and under the protection of inert gas, heat the reaction to obtain burr-shaped polyacrylamide nanospheres; the heating reaction temperature is 65°C and the time is 4 hours; the amounts of thiolated PAMAM loaded with metal copper quantum dots, surfactant, acrylamide, acrylic acid, and crosslinking agent are as follows by mass: 1 part of thiolated PAMAM loaded with metal copper quantum dots, 2 parts of surfactant, 13 parts of acrylamide, 7 parts of acrylic acid, and 3 parts of crosslinking agent.

[0077] Example 10

[0078] A method for preparing burr-shaped polyacrylamide nanospheres comprises the following steps:

[0079] (1) Adding thiolated PAMAM to a chloroform solution of metal copper quantum dots with an average particle size of 3 nm, ultrasonically dispersing, and drying to obtain thiolated PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to the thiolated PAMAM is 0.02:1; the ultrasonic power is 160 W, and the ultrasonic temperature is 40°C; the specific preparation process of thiolated PAMAM is: adding methyl thioglycolate to the aqueous solution of aminated PAMAM, stirring the reaction, and drying under reduced pressure to obtain the thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.3; the stirring reaction temperature is 50°C, and the reaction time is 8 hours;

[0080] (2) Dispersing the thiolated PAMAM loaded with metal copper quantum dots and the surfactant polyvinyl pyrrolidone in an organic solvent and stirring evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 1.6 h;

[0081] (3) Add acrylamide and acrylic acid monomers and cross-linking agent N,N-methylenebisacrylamide to the premixed solution and stir evenly; and under the protection of inert gas, heat the reaction to obtain burr-shaped polyacrylamide nanospheres; the heating reaction temperature is 55°C and the time is 4 hours; the amounts of thiolated PAMAM loaded with metallic copper quantum dots, surfactant, acrylamide, acrylic acid, and cross-linking agent are as follows by mass: 1 part of thiolated PAMAM loaded with metallic copper quantum dots, 2 parts of surfactant, 13 parts of acrylamide, 7 parts of acrylic acid, and 2 parts of cross-linking agent.

[0082] Embodiment 11

[0083] A method for preparing burr-shaped polyacrylamide nanospheres comprises the following steps:

[0084] (1) Adding thiolated PAMAM to a chloroform solution of metal copper quantum dots with an average particle size of 3 nm, ultrasonically dispersing, and drying to obtain thiolated PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to the thiolated PAMAM is 0.02:1; the ultrasonic power is 160 W, and the ultrasonic temperature is 40°C; the specific preparation process of thiolated PAMAM is: adding methyl thioglycolate to the aqueous solution of aminated PAMAM, stirring the reaction, and drying under reduced pressure to obtain the thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.3; the stirring reaction temperature is 50°C, and the reaction time is 8 hours;

[0085] (2) Dispersing the thiolated PAMAM loaded with metal copper quantum dots and the surfactant polyvinyl pyrrolidone in an organic solvent and stirring evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 1.6 h;

[0086] (3) Add acrylamide and acrylic acid monomers and crosslinking agent N,N-methylenebisacrylamide to the premixed solution and stir evenly; and heat the reaction under the protection of inert gas to obtain burr-shaped polyacrylamide nanospheres; the heating reaction temperature is 75°C and the time is 4 hours; the amounts of thiolated PAMAM loaded with metal copper quantum dots, surfactant, acrylamide, acrylic acid, and crosslinking agent are as follows by mass: 1 part of thiolated PAMAM loaded with metal copper quantum dots, 2 parts of surfactant, 13 parts of acrylamide, 7 parts of acrylic acid, and 2 parts of crosslinking agent.

[0087] Example 12

[0088] A method for preparing burr-shaped polyacrylamide nanospheres comprises the following steps:

[0089] (1) Adding thiolated PAMAM to a chloroform solution of metal copper quantum dots with an average particle size of 3 nm, ultrasonically dispersing, and drying to obtain thiolated PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to the thiolated PAMAM is 0.02:1; the ultrasonic power is 160 W, and the ultrasonic temperature is 40°C; the specific preparation process of thiolated PAMAM is: adding methyl thioglycolate to the aqueous solution of aminated PAMAM, stirring the reaction, and drying under reduced pressure to obtain the thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.3; the stirring reaction temperature is 50°C, and the reaction time is 8 hours;

[0090] (2) Dispersing the thiolated PAMAM loaded with metal copper quantum dots and the surfactant polyvinyl pyrrolidone in an organic solvent and stirring evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 1.6 h;

[0091] (3) Add acrylamide and acrylic acid monomers and crosslinking agent N,N-methylenebisacrylamide to the premixed solution and stir evenly; and heat the reaction under the protection of inert gas to obtain burr-shaped polyacrylamide nanospheres; the heating reaction temperature is 65°C and the time is 4 hours; the amounts of thiolated PAMAM loaded with metal copper quantum dots, surfactant, acrylamide, acrylic acid, and crosslinking agent are as follows by mass: 1 part of thiolated PAMAM loaded with metal copper quantum dots, 2 parts of surfactant, 13 parts of acrylamide, 7 parts of acrylic acid, and 2 parts of crosslinking agent.

[0092] Comparative Example 1

[0093] A method for preparing burr-shaped polyacrylamide nanospheres comprises the following steps:

[0094] (1) Adding thiolated PAMAM to a chloroform solution of metal copper quantum dots with an average particle size of 3 nm, ultrasonically dispersing, and drying to obtain thiolated PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to the thiolated PAMAM is 0.02:1; the ultrasonic power is 160 W, and the ultrasonic temperature is 40°C; the specific preparation process of thiolated PAMAM is: adding methyl thioglycolate to the aqueous solution of aminated PAMAM, stirring the reaction, and drying under reduced pressure to obtain the thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.3; the stirring reaction temperature is 50°C, and the reaction time is 8 hours;

[0095] (2) Dispersing the thiolated PAMAM loaded with metal copper quantum dots in an organic solvent and stirring evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 1.6 h;

[0096] (3) Add surfactant polyvinyl pyrrolidone, acrylamide and acrylic acid monomers, and crosslinker N,N-methylenebisacrylamide to the premixed solution and stir evenly; and heat the reaction under the protection of inert gas to obtain burr-shaped polyacrylamide nanospheres; the heating reaction temperature is 65°C and the time is 4 hours; the amounts of thiolated PAMAM loaded with metal copper quantum dots, surfactant, acrylamide, acrylic acid, and crosslinker are as follows by mass: 1 part of thiolated PAMAM loaded with metal copper quantum dots, 2 parts of surfactant, 13 parts of acrylamide, 7 parts of acrylic acid, and 2 parts of crosslinker.

[0097] Comparative Example 2

[0098] A method for preparing burr-shaped polyacrylamide nanospheres comprises the following steps:

[0099] (1) Add thiolated PAMAM to a chloroform solution of metal copper quantum dots with an average particle size of 3 nm, ultrasonically disperse, and dry to obtain thiolated PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to the thiolated PAMAM is 0.1:1; the ultrasonic power is 160 W, and the ultrasonic temperature is 40°C; the specific preparation process of thiolated PAMAM is: add methyl thioglycolate to the aqueous solution of aminated PAMAM, stir to react, and dry under reduced pressure to obtain thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to methyl thioglycolate is 1:1.3; the stirring reaction temperature is 50°C, and the reaction time is 8 hours;

[0100] (2) Dispersing the thiolated PAMAM loaded with metal copper quantum dots and the surfactant polyvinyl pyrrolidone in an organic solvent and stirring evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 1.6 h;

[0101] (3) Add acrylamide and acrylic acid monomers and crosslinking agent N,N-methylenebisacrylamide to the premixed solution and stir evenly; and heat the reaction under the protection of inert gas to obtain burr-shaped polyacrylamide nanospheres; the heating reaction temperature is 65°C and the time is 4 hours; the amounts of thiolated PAMAM loaded with metal copper quantum dots, surfactant, acrylamide, acrylic acid, and crosslinking agent are as follows by mass: 1 part of thiolated PAMAM loaded with metal copper quantum dots, 2 parts of surfactant, 13 parts of acrylamide, 7 parts of acrylic acid, and 2 parts of crosslinking agent.

[0102] Performance Testing:

[0103] The burr-shaped polyacrylamide nanospheres prepared in Examples 1-12 and Comparative Examples 1-2 were dispersed in white oil, and their initial particle sizes were determined by laser particle size analyzer. The nanospheres prepared in Examples 1-12 and Comparative Examples 1-2 were then dispersed in simulated formation water with a mineralization of 30,000 mg / L, and expanded at 80°C for different times, and their expansion multiples were determined. The results are shown in Table 1.

[0104] Low permeability cores were selected for evaluation of oil displacement effect: the cores were first saturated with simulated formation water to determine their pore volume; then the cores were saturated with simulated crude oil; the cores were displaced with simulated formation water until the outlet end stopped producing oil, and the recovery factor A was determined; a burr-shaped polyacrylamide nanosphere dispersion was injected into the cores and placed at 65°C for 5 days; the cores were displaced with simulated formation water again until the outlet end stopped producing oil, and the recovery factor B was determined; the recovery factor increase was C (%) = (BA) / AX 100%, and the results are shown in Table 1.

[0105]

[0106] Depend on Figure 1It can be seen that the present invention has prepared burr-like polyacrylamide nanospheres, the surface of the nanospheres has a spike-like structure, and some of the burrs present a certain lamellar structure, which is conducive to the formation of an interfacial film during the oil displacement process. The formation of the above structure increases the specific surface area of ​​the nanospheres. During the water absorption and expansion process, the larger specific surface area can effectively disperse the internal stress and prevent stress concentration from occurring, which leads to the rupture of the nanospheres; moreover, the burr structure after water absorption and expansion is conducive to mutual entanglement, thereby improving the plugging rate. More importantly, under the action of the reservoir rock surface, the polyacrylamide nanospheres with a burr-like structure can be further adsorbed and form an interfacial film, which prevents oil droplets from re-adhering to the rock surface with the help of the barrier effect of the film. The formation of structural separation pressure reduces the force between the oil droplets and the rock and the flow resistance of crude oil in the reservoir, thereby improving the recovery rate. Comparative Example 1 shows that the outer layer of the PAMAM dendrimer has a large number of hydrophilic groups such as ester groups and amide groups, while the hydrocarbon chain inside is a lipophilic group; therefore, PAMAM exhibits strong hydrophilicity. In order to improve the dispersion performance of the thiolated PAMAM loaded with metal copper quantum dots, it is necessary to disperse the surfactant commonly used in the nanosphere polymerization process in advance with the thiolated PAMAM loaded with metal copper quantum dots in an organic solvent to prevent PAMAM from agglomerating or even settling. Figure 2 It can also be seen that due to the poor dispersibility of the thiol-modified PAMAM loaded with metallic copper quantum dots, it is unable to play a role in uniform nucleation, the particle size of the prepared nanospheres is relatively large, and it is unable to form a burr-like structure. Only a small amount of granular material is generated on the surface of the large microspheres, and the oil recovery efficiency is greatly reduced. At the same time, it can be seen from Comparative Example 2 that due to the high activity of metallic copper quantum dots, there is a strong quantum dot effect. When too much metallic copper quantum dots are added, it is not only not conducive to dispersion, but also causes a large number of quantum dots to adhere to the outer surface of PAMAM, affecting the expansion stability of the nanospheres and the improvement of oil recovery efficiency. Figure 3 It can also be seen that when too many quantum dots are added, they cannot be evenly loaded onto the surface of the thiolated PAMAM, which can easily lead to agglomeration between the quantum dots, and cannot provide gaps to differentiate the polymerization rate, and cannot form a burr-like structure; and the formed nanospheres have extremely irregular morphology, and a large number of stacked structures appear.

[0107] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing burr-shaped polyacrylamide nanospheres, characterized in that: The following steps are involved: (1) adding thiolated PAMAM to a metallic copper quantum dot solution, performing ultrasonic dispersion, and drying to obtain thiolated PAMAM loaded with metallic copper quantum dots; the mass ratio of the metallic copper quantum dots to the thiolated PAMAM is (0.001-0.05):1; (2) dispersing the thiol-PAMAM loaded with metal copper quantum dots and a surfactant in an organic solvent and stirring evenly to obtain a premixed solution; (3) Add acrylamide and acrylic acid monomers and a cross-linking agent to the premixed solution and stir evenly; and heat the premixed solution under the protection of an inert gas to obtain burr-shaped polyacrylamide nanospheres.

2. The method for preparing burr-shaped polyacrylamide nanospheres according to claim 1, characterized in that: The specific preparation process of the thiolated PAMAM in step (1) is as follows: adding thioglycolic acid or methyl thioglycolate to the aqueous solution of amino PAMAM, stirring for reaction, and drying under reduced pressure to obtain the thiolated PAMAM.

3. The method for preparing burr-shaped polyacrylamide nanospheres according to claim 2, characterized in that: The aminated PAMAM is a PAMAM of 4-10 integer generations.

4. The method for preparing burr-shaped polyacrylamide nanospheres according to claim 2, characterized in that: The molar ratio of the amino group on the aminated PAMAM to thioglycolic acid or methyl thioglycolate is 1:(1.1-1.5).

5. The method for preparing burr-shaped polyacrylamide nanospheres according to claim 2, characterized in that: The stirring reaction temperature is 45-55°C and the reaction time is 7-10h.

6. The method for preparing burr-shaped polyacrylamide nanospheres according to claim 1, characterized in that: The surfactant in step (2) is polyvinyl pyrrolidone; and the cross-linking agent in step (3) is N,N-methylenebisacrylamide.

7. The method for preparing burr-shaped polyacrylamide nanospheres according to claim 1, characterized in that: The heating reaction temperature in step (3) is 55-75°C and the time is 2-6h.

8. The method for preparing burr-shaped polyacrylamide nanospheres according to claim 1, characterized in that: The amounts of thiolated PAMAM loaded with metallic copper quantum dots, surfactant, acrylamide, acrylic acid and crosslinking agent are respectively as follows by mass: 1 part of thiolated PAMAM loaded with metallic copper quantum dots, 1-3 parts of surfactant, 10-15 parts of acrylamide, 5-10 parts of acrylic acid and 1-3 parts of crosslinking agent.

9. A burr-shaped polyacrylamide nanosphere, characterized in that: The burr-shaped polyacrylamide nanospheres are prepared by the preparation method of any one of claims 1 to 8.

10. Use of the burr-shaped polyacrylamide nanospheres according to claim 9 as a profile control and oil displacement agent.

Citation Information

Patent Citations

  • Preparation method of core-shell type fluorescent microsphere profile control and plugging agent applied to offshore oilfield high-permeability reservoir based on quantum dots

    CN115181217A

  • Quantum dot light-emitting film, preparation and application of quantum dot light-emitting film in white-light Mini-LED device

    CN115247060A

  • Application of quantum dots in unconventional oil reservoir exploitation, oil-displacing agent and method for increasing yield by using oil-displacing agent

    CN115306362A

  • High-brightness and high-stability water-soluble quantum dot fluorescent microsphere and preparation method thereof

    CN117736722A

  • Temperature-resistant and salt-resistant polymer microsphere and preparation method thereof

    CN118580443A